Mental health and sleep quality among patients with asthma and COPD - Aldabayan, Yousef Saad (Frontiers in Medicine, 2023)
This study aims to compare the mental health of patients with asthma and COPD in terms of anxiety, depression, and sleep quality and to examine the factors that predict sleep disturbance, anxiety, and depressive symptoms. Methods This quantitative cross-sectional study employed convenience sampling to enroll 200 patients with asthma and 190 patients with COPD. Data were gathered using a standardized self-administered questionnaire that contained sections on patients’ characteristics, the Sleep Quality, Anxiety, and Depression. Results The prevalence of poor sleep quality was 17.5 and 32.6% among asthmatic and COPD patients, respectively. The incidence of anxiety and depression was 38 and 49.5% among the patients with asthma, respectively. Their prevalence in patients with COPD was 48.9 and 34.7%, respectively. The multivariate regression analysis showed that marital status (married), BMI, education level (pre-university level), presence of comorbid illness, and depression were significant predictors of PSQI in asthmatic patients. Moreover, age, gender (male), marital status (married), education level (pre-university level), depression, and anxiety were significant predictors of PSQI among COPD participants. According to this study, COPD, and asthma pose serious health risks, including reduced sleep quality, anxiety, and depression.